Troubled Tariffs : Revisiting Water Pricing for Affordable and Sustainable Water Services - Andres, Luis A.; Saltiel, Gustavo; Misra, Smita; Joseph, George; Lombana Cordoba, Camilo; Thibert, Michael; Fenwick, Crystal (World Bank, Washington, DC, 2021)
Tariffs are essential but not the only pathway to cost recovery, addressing affordability, and managing water conservation. To maximize their potential, they must be well designed, complemented by appropriate instruments, adequately regulated, and understood by customers. This report builds upon that one, and provides policy makers with the information needed to design better tariffs to further the economic efficiency, affordability, and environmental sustainability of water supply services. Through a layered and comprehensive analysis of the most prevalent tariff structures, it provides policy makers with specific guidance on pricing water supply services in response to the sector’s often-competing goals. This document comprises a synthesis of fifteen unique research papers that, combined, articulate a step-by-step thought process for designing effective tariffs with a view to achieving sustainable development goal (SDG) 6.